PEMBELAJARAN MENULIS (INSYAâ) Dengan Pendekatan Komunikatif-Interaktif di Sekolah Tinggi Agama Islam Negeri Ponorogo - Yufridal, Yufridal (Kodifikasia, 2014)
Abstrak:Writing skills are used to record, recording, convincing, report, inform, and influence the reader. The purpose and goal of the study can only be achieved by either by the learners who can compose and assemble the mind and bring it in writing with a clear, smooth, and communicative. This clarity depends on the mind, organization, usage and word choice, and sentence structure. Write essays (Insha) may be regarded as the most difficult skill than premises other language skills. What a student using a second or foreign language orally (syafawi), then a native speaker can understand and accept less than perfect pronunciation or phrases that are less appropriate or even incomÂpatible with the rules grametikal. However, when learning a second language use/foreign kitabi, the native speakers who read it will be harder assess writing a lot of spelling or grammar errors. Although the meaning is conveyed was quite clear and his pretty neat, but a written essay is required to be good and as far as possible without errors because thought to reflect the level of education concerned shall essay writer.Kata Kunci: Insyaâ, Pendekatan Komunikatif-Interaktif, STAIN Ponorogo